Analysis of factors influencing the awareness of inpatients regarding hospital clinical pharmacy services and willingness to pay: a multicenter survey in Hebei Province, China - Yang, Ruixia; Wang, Xin; Wu, Huizhen; Sun, Qian; Zhang, Sijie; Dong, Qian; Li, Mengjiao; Xu, Xiaoli; Bai, Jing; Liang, Ping; Hou, Juan (Frontiers in Pharmacology, 2025)
IntroductionPharmacists are increasingly adopting patient-centered roles, improving healthcare outcomes by reducing medication errors and costs. In China, recent healthcare reforms recognize and compensate for pharmacy services. However, patient awareness of these services and their willingness to pay (WTP) remain underexplored. Therefore, this study aims to examine inpatient understanding of pharmacy services, their WTP in Hebei Province, and the factors affecting it.MethodsBetween July and August 2024, a questionnaire was used to survey inpatients from 22 medical institutions across 11 prefecture-level cities in Hebei Province regarding their awareness of WTP for pharmacy services. Further investigation targeted inpatients unwilling to pay. The survey results were analyzed descriptively, with frequencies and percentages (%) used for categorical data and continuous data were presented as mean ± standard deviation (X ± SD). The chi-square test was used to determine statistically significant influences, and logistic regression analysis was performed to identify significant factors affecting inpatient WTP for pharmacy services. A column-line graph was validated using receiver operating characteristic curves and calibration graph analysis.ResultsIn total, 464 questionnaires were distributed, with 432 valid responses, yielding a 93.10% effective response rate. Most inpatients (89.58%) viewed hospital pharmacists as primarily responsible for dispensing medication, while only 5.79% were aware of broader pharmacy services. Despite this, 72.69% of the inpatients were willing to receive pharmacy services, and 95.38% of those who had received such services found them beneficial. Half of the inpatients (216, or 50.00%) indicated WTP for pharmacy services. Among those initially unwilling to pay (216 inpatients), 102 indicated they would consider payment if a doctor recommended clinical pharmacist guidance. Of the 318 inpatients who were WTP, 315 (99.06%) chose health insurance reimbursement as a payment method. Key factors influencing inpatient WTP included literacy level, preferred source of medication counseling, prior pharmacy service experience, understanding of pharmacy service policies, and readiness to recommend these services (P < 0.05).ConclusionMost inpatients lacked knowledge and trust in clinical pharmacists, with limited awareness of the value of pharmacy services. However, they demonstrated high acceptance and WTP for these services, with nearly all inpatients preferring health insurance reimbursement. Integrating pharmacy service fees into health insurance is crucial for promoting these services.